Foaming and defoaming properties of CO2‐switchable surfactants. Issue 4 (7th June 2022) - Poole, Hailey; Jessop, Philip G.; Stubenrauch, Cosima
Abstract: The present study is about the foaming and defoaming properties of the CO2 ‐switchable surfactant N, N‐dimethyltetradecylamine (C14 DMA) and its advantages compared with the non‐switchable counterpart tetradecyltrimethylammonium bromide (C14 TAB). In the absence of CO2, C14 DMA is a water insoluble organic molecule without any surface activity thus being unable to stabilize foams. In the presence of CO2, the head group becomes protonated which transforms the water insoluble molecule into a cationic surfactant. Comparing the surface properties and foamability of C14 DMA and C14 TAB one finds a very similar behavior. However, the foam stabilities differ depending on the gas. Foaming the two‐surfactant solutions with CO2 leads to very unstable foams in both cases. However, foaming the two surfactant solutions with N2 reveals the switchability of C14 DMA: while the volume of foams stabilized with C14 TAB hardly changes over 1600 s, the volume of foams stabilized with C14 DMA decreases significantly in the same period of time. This difference is due to the fact that the surface activity, that is, the amphiphilic nature, of C14 DMA is continuously switching off since CO2 is displaced by N2 thus deprotonating and deactivating the surfactant.